Never drop your guard down after atrial septal defect closure: a case report. Issue 2 (7th June 2019) - Bergonti, Marco; Toscano, Olga; Teruzzi, Giovanni; Trabattoni, Daniela
Abstract: Background: Percutaneous atrial septal defect (ASD) closure carries a not negligible burden of complications, such as the erosion of cardiac structures surrounding the device. Complications related to erosion are rare and often occur during the first 6 months after implantation. Case summary: A 40-year-old female patient underwent percutaneous ASD closure in 2006. After 12 years of uneventful follow-up, in March 2018, a device dislodgement causing atrial shunting was incidentally discovered and was attributed to device-induced atrial septal erosion. The patient successfully underwent surgical removal of the device and correction of the interatrial defect. Discussion: Our purpose is to underline the importance of staged long-term imaging follow-up, even many years after a successful procedure and to highlight the possible risk factors leading to this worrisome condition. In addition, we sought to underline the possible risks associated with deficient aortic rim and explain pros and cons of different approaches.